Àsùwàda Principle and Inter-Ethnic Conflict in Nigeria - Yunusa Kehinde Salami (Yoruba Studies Review)
This paper examines the àsùwàdà principle as an indigenous social theory, which is based on alásùwàdà, a body of doctrines according to which the creator of human beings and everything in nature, dá (created) individual human beings as à-sù-wà (beings who can only live successfully as part of a human group with a purpose). By establishing a teleological or purposeful unity and interconnectedness among all human beings, the àsùwàdà principle suggests that all human beings are created to be gregarious in nature and enjoy the best ìwà (existence or character) when they sù-wà (live in group). This paper interrogates the àsùwàdà principle in relation to the problem of ethnic conflicts in Nigeria. The paper concludes that if as human beings, we are dá (created) to be àsùwà, then, with the complementary ideas of alájọbí, alájọgbé, and ìfọgbọ́ntáyéṣe, ethnic pluralism should not necessarily lead to ethnic antagonism or conflict.